Pengaruh Model Problem Based Learning Terhadap Kemampuan Berpikir Kritis Pada Pembelajaran IPAS Kelas V Sekolah Dasar Negeri 24 Pontianak Tenggara - Alya Amini; Kartono Kartono; Dyoty Auliya Vilda Ghasya (Journal on Education, 2024)
This research aims to analyze the influence of the Problem Based Learning model on students' critical thinking abilities in class V and science learning at Elementary School. The research method used Quasi-Experimental Design with the Nonequivalent Control Group Design type. The population is class V of the State Elementary School 24 Southeast Pontianak. The sampling technique is Probability Sampling with the Simple Random Sampling type. The data collection technique used is a measurement technique and the data collection tool is a written test in the form of an essay. Based on data analysis, the average results of the final tests for the experimental class and control class were obtained. The results of hypothesis testing using the independent sample t-test obtained sig 0.289 > 0.05 so that Hₒ was rejected and Hₐ was accepted. This proves that there is an influence of the Problem Based Learning model on students' critical thinking abilities in science learning. Based on the results of effect size obtained 0.417 which is included in the moderate criteria. Thus, it can be concluded that the Problem Based Learning model provides a fairly helpful influence on students' critical thinking skills in science learning for class V of Elementary School.